Preference for Distinct Variants in Learning Sound Correspondences During Dialect Acquisition - Yu, Xiaoyu; Do, Youngah (Language and speech, 2025)
Sound correspondences (SCs) have been found to be learnable phonological patterns in second dialect acquisition. Cross-linguistically, SCs consist of similar as well as distinct variants. However, in the study of SC learning, the effect of the similarity between the corresponding variants remains understudied. The salience hypothesis proposes that distinct dialect variants are more salient and learnable, while the learning bias hypothesis in phonological learning predicts that SC patterns with similar variants are preferred by learners. We conducted an artificial language learning experiment to test how sound similarity affects SC learning. Specifically, the degrees of similarity between variants were evaluated from multidimensional metrics, including phonetic and phonological measures, which are cross-validated with typological evidence. While there was no effect of variant similarity in learning simple one-to-one SCs, a preference for the most distinct dialect variant was found in the learning of SCs exhibiting more complex mapping structures (i.e., two-to-one and one-to-two). Our results confirm a preference for distinct variants in SC learning, although this effect relies on two conditions. First, the preference for distinction emerges only in the presence of complex mapping structures. Second, this preference requires an activation threshold, in that the distance of the SC must be sufficiently large to trigger the effect.